English Football in Teams in Inter-War Romania: Football and International Exchanges in the 1930s. Issue 9 (3rd July 2019) - Rotar, Marius; Ursu, Vasile Emil
Abstract: The development of football in interwar Romania can be noticed in many ways: the growth in the number of teams and players, the growing football audiences, the increased number of international matches played abroad and at home by the national team and also by the Romanian club teams. In this respect, it is no accident that the Romanian national football team attended all the interwar editions of the World Cup (1930, 1934, and 1938). The aim of this article is to analyse the contacts between the Romanian and English interwar football, materialized through the close season tours of several English football teams in Romania (Oxford City, 1927; Liverpool, 1936; Leicester City, 1937 and Preston North End, 1938). These tours represented a great opportunity to assess the level of Romanian football and were also a good propaganda for sport and football during those times. Likewise, these tours prepared the first international match between Romania and England, played in Bucharest in 1939. Some comparisons with similar situations of other sports practiced in interwar Romania are also invoked.